Slope instability hazard and risk analysis under the influence of anthropogenic global warming: proposal for a methodological approach - Mora, Sergio (2021)
Rainfall rates may be modified, in the mid to long term in some microclimates, by the influence of anthropogenic global warming (AGW). If true in areas with unstable hydric balances AGW is likely to become superimposed to climate variability and other hazards, both natural and human: vulnerability, earthquakes, volcanoes, urban and infrastructural expansion, El Niño-La Niña-ENSO, land degradation. Slope instability hazards may become more destructive socially, economically, and environmentally. It is critical to redefine priorities in policy, decision-making, and risk management. An analytical procedure is proposed for areas with microclimate conditions prone to escalate rainfall intensity, duration, frequency, volume, and its resulting hydric unbalances. Progressive rises in water table and interstitial pressure resulting from intense rainfalls, with smaller return periods, may lead to higher water tables and earlier conditions for slope failure. Risk management, supported by Engineering Geology must focus on reducing and transferring risk and decrease vulnerability, as the best adaptation instrument to face any hazard.